Party System Crisis: The Exhaustion of Chile’S Spine - Navarrete-Yanez, B (Springer Nature Brazil, 2021)
From a comparative historical perspective, this chapter examines the Chilean political party system post-transition and how they lost their role in the political competition and in the articulation of interests in the country. The analysis focuses on the transformations that political parties have suffered in the last 30 years that have led to the dissolution of one of the main pieces of the “Chilean Model.” The inability to process the new demands of Chilean society, the rigid organizational architecture, the emptying of party structures, and the erosion of programmatic borders, configure overall the exhaustion of the Chilean system. © 2021, The Author(s), under exclusive license to Springer Nature Switzerland AG.